2020
DOI: 10.1155/2020/6726147
|View full text |Cite
|
Sign up to set email alerts
|

Combat Mobile Evasive Malware via Skip-Gram-Based Malware Detection

Abstract: Android malware detection is an important research topic in the security area. There are a variety of existing malware detection models based on static and dynamic malware analysis. However, most of these models are not very successful when it comes to evasive malware detection. In this study, we aimed to create a malware detection model based on a natural language model called skip-gram to detect evasive malware with the highest accuracy rate possible. In order to train and test our proposed model, we used an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…The dividing characteristic with the greatest gain ratio is chosen [ 1 ]. The nonleaf nodes of the produced decision tree are regarded as significant characteristics [ 30 ]. The authors combined decision trees and neural networks, resulting in an increase in classification results.…”
Section: Attribute Extraction Methodsmentioning
confidence: 99%
“…The dividing characteristic with the greatest gain ratio is chosen [ 1 ]. The nonleaf nodes of the produced decision tree are regarded as significant characteristics [ 30 ]. The authors combined decision trees and neural networks, resulting in an increase in classification results.…”
Section: Attribute Extraction Methodsmentioning
confidence: 99%
“…rough this process, it classifies samples and regresses a binary division into classification, continuation, or numerical types. As a result of this study, the DT algorithm was used the fourth most [32,37,39,44,46,47,53,56,58,59,62,64,65,68,71,72,75,76,78,85,86,92,96,98,101,111,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134].…”
Section: 31mentioning
confidence: 99%
“…e study assessed both the MalGenome and private datasets and identified that the BN and RD scored 99.7% and 93.03%, respectively, for the TPR. Egitmen et al [39] used Android software with artificially generated text to classify modern Android malware, but applied a skip-gram technique configured for NLP to extract useful features. is study also demonstrated that the NLP-based static analysis approach for application source code has promising results.…”
Section: Rq3 What Are the Limitations Of The Current Research?mentioning
confidence: 99%
“…It turns out that the predictive ability of integrated classifiers is much better than that of individual classifiers in general. In the studies using the ensemble classifier, there are two directions: one is to directly use related ensemble classifiers, such as random forest (RF) [36], gradient boosting decision tree (GBDT) [37], and AdaBoost [38]; the other is to use ensemble methods to combine with single classifiers, such as boosting, bagging, and stacking methods. Yerima and Sezer [39] proposed a detection framework, DroidFusion, based on multilevel classifier fusion.…”
Section: Related Workmentioning
confidence: 99%